Penetrating the Culinary Market Through Sharia Marketing Strategies - Mega Tunjung Hapsari; Siti Kalimah (Create: Journal of Islamic Management and Business, 2025)
This study explores the implementation of the 12P marketing mix strategy in a home-based catering business as a means to increase sales volume in a competitive culinary market. Despite limited managerial and financial resources, the business under study successfully adopted an integrated marketing approach encompassing product planning, pricing, branding, servicing, promotion, and distribution. The research employs a qualitative descriptive method, collecting data through interviews, observations, and documentation with the business owner, employees, and customers. Results indicate that consistent taste quality, flexible and customizable product offerings, responsive customer service, and simple yet impactful digital promotion are key drivers of success. Conversely, challenges such as delayed customer payments, labor limitations during peak orders, and the absence of documented procedures hinder operational efficiency. A surprising finding is that sophisticated marketing strategies, often associated with large corporations, can be effectively applied in micro-businesses when grounded in empathy, local context, and service ethics. Theoretically, this study contributes to the expansion of service marketing literature by validating the practical relevance of the 12P framework for micro-enterprises, especially in the food service sector. Practically, the study offers a replicable model for small business owners to enhance customer satisfaction and sustain growth using accessible tools and strategies. Limitations of the study include its single-case scope and qualitative nature, inviting future research with broader and more quantitative designs.